An Ultra-Low-Leakage Microcontroller With Configurable Power Management for Energy Harvesting IoT Devices - Shima Sedighiani; Bram van Bolderik; Barry de Bruin; Kamlesh Singh; Roel Jordans; Pieter Harpe; Jose Pineda de Gyvez (IEEE Access)
This paper presents a power management unit (PMU) architecture designed for energy-harvesting IoT devices, integrating a dual-capacitor system, an ultra-low-leakage balloon-based microcontroller (MCU), and a fully digital controller. The PMU dynamically switches between an active capacitor, an idle capacitor, and a backup battery, optimizing energy use in different operational modes. This configuration optimizes capacitor voltages for various operational modes, applying a higher voltage to the active capacitor for enhanced performance and a lower voltage to the idle capacitor for ultra-low-leakage data retention. Additionally, a fully digital PMU controller replaces conventional analog components, leveraging a digital voltage monitor and converter-free voltage regulation. The test chip is designed and fabricated using a 28-nm FD-SOI technology. The balloon-based MCU measurement shows that it can retain data during idle mode with a power consumption of only 3nW at 0.6V, achieving a $4400 × $ reduction in leakage power compared to conventional MCUs without balloon memory. Furthermore, the results of the system measurement demonstrate a substantial reduction in battery usage from 88% in traditional setups to 0%, while ensuring continuous operation and data retention.